Association between neurological outcome and poststroke comorbid mood and anxiety disorders: A real‐life experience. Issue 6 (5th May 2021) - Rabat, Yolaine; Houeze, Richard; Sagnier, Sharmila; Olindo, Stephane; Poli, Mathilde; Debruxelles, Sabrina; Renou, Pauline; Rouanet, François; Berthoz, Sylvie; Sibon, Igor
Abstract: Introduction: Poststroke depression (PSD) and anxiety (PSA) are prevalent and have a strong impact on functional outcome. Beside stroke severity, little is known on their clinical determinants. This study investigated the association between stroke mechanism, neurological poststroke complications and remaining vascular risk factors and the presence of comorbid PSD and PSA, termed poststroke emotional distress (PSED). Methods: This was a retrospective analysis of a prospectively compiled medical records database of consecutive patients evaluated during a follow‐up visit 3‐ to 4‐month poststroke. HAD scale was used to define PSED category (PSD+PSA vs. NoPSD+NoPSA). Stroke mechanism and poststroke complications were identified clinically or using appropriate scales. Their association with PSED was tested using a multivariate logistic regression model. Results: The sample included 2, 300 patients (male: 64.8%); 19% had a PSED and 56.39% were free of any depression or anxiety. The most frequent poststroke complications were fatigue/fatigability (58.4%), sleep problems (26.7%), and pain (20.4%). While no association was observed between PSED and stroke mechanism, higher functional disability (OR:1.572), lower cognitive abilities (OR:0.953), sleep problems (OR:2.334), pain (OR:1.478), fatigue/fatigability (OR:2.331), and abnormal movements (OR:2.380) were all independent risk factors. Persisting tobacco consumption (OR:1.360) was the only vascular significant risk factor. Conclusions: The frequency of comorbid PSED remains high (1/5 patient) despite improved awareness of these conditions. The association between poststroke complications and the presence of PSED emphasizes the need for standardized neurological and psychological evaluations at follow‐up. These results foster the need to improve the management of addictive behaviors to reduce the burden of PSED. Abstract : The frequency of comorbid PSED remains high (1/5 patient) despite improved awareness of these conditions. Most of poststroke complications were independently associated with the presence of PSED emphasizing the need for standardized neurological evaluations at follow‐up.